THE EFFECT OF COMPENSATION AND WORKLOAD ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT ( Study at the Department Fire Extinguisher Surabaya City Fire and Rescue ): PENGARUH KOMPENSASI DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI MELALUI KOMITMEN ORGANISASI (Studi pada Dinas Pemadam Kebakaran dan Penyelamatan Kota Surabaya ) - Wasis Sutikno; Dewie Tri Wijayati Wardoyo; Andre Dwijanto Witjaksono (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The background of this research is the existence of compensation factors, workload, and organizational commitment which are felt to be an influence on employee performance. These three factors are considered to be things that can improve and decrease employee performance. Compensation is an appreciation from the organization that is received by employees as an appreciation for their contribution to the institution. Workload shows the average activity of a job in a certain period of time, while organizational commitment as an interverning variable in relation to compensation and workload on employee performance. The study aims to see the influence of compensation and workload on employee performance through organizational commitment as a connecting variable in the Surabaya City Fire and Rescue Service. The researcher formulated the following research hypothesis: (1) Is the compensation significant for organizational commitment? (2) Does workload have a significant effect on organizational commitment? (3) Does compensation have a significant effect on employee performance? (4) Does workload affect employee performance? (5) Does organizational commitment affect employee performance? (6) Does organizational commitment mediate the effect of compensation on employee performance? (7) Do organizational committees mediate the effect of workload on employee performance? This study uses a quantitative approach with an associative type. The data collection technique uses questionnaires and interview methods on related sources. The method used by the researcher in processing data using the SEM Structure Equation Model with the help of PLS processing. Based on the results of the study, it was found that the compensation obtained by the Surabaya City Fire and Rescue Service had a significant effect on the Organizational Commitment they felt. The workload borne by the Surabaya City Fire and Rescue Service has no effect and is not significant to the Organizational Commitment they feel. The compensation obtained by the Surabaya Fire and Rescue Service has a significant effect on the performance of the employees they produce. The workload borne by the Surabaya City Fire and Rescue Service has a significant effect on the performance of the employees they produce. The organizational commitment felt by the Surabaya City Fire and Rescue Service has a significant effect on the performance of the employees they produce. The compensation obtained by the Surabaya City Fire and Rescue Service has a significant effect on the Employee Performance they produce through Organizational Commitment as an intermediary variable or moderation. The workload borne by the troops of the Surab City Fire and Rescue Service